ESTIMASI BIAYA PROYEK KONSTRUKSI GEDUNG OLEH QUANTITY SURVEYOR (STUDI KASUS: PEKERJAAN STRUKTUR ATAS PROYEK APARTEMENT THE ACCENT JAKARTA) - Ariani, Vivi; Peli, Martalius; Fitri, Dinni Fadhilah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2018)
Abstract : Cost Estimating of the upper structure on each construction project is usually done by the civil engineer or architect. However, as the development of science, new professions such as Quantity Surveyor have shifted the task of civil engineering or architects in making cost estimates. The QS profession is a profession that has the ability to analyze the cost and practical components of theproject's physical construction work in a successful way so as to apply its analytical results in solving the problems typical for each project. The case study of this research is the top structural work on the accent Apartments built on an area of 3,300 m2 with a building area of 27,000 m2. Research methodology by literature study and The Accent volume calculation using standard measurement method (SMM), while for unit price partly taken from the reference of PU Permen 2007. From the analysis of volume calculation and unit price analysis, the total cost of the structural work top of Rp. 51,162,851,482.23 with the price per m2 is 2.084,412.47 / m2. Duration of implementation is for 16 months. For cash flow, cash in consists of a 10% down payment, 5% retention, monthly employment progress minus downpayment and retention, and an office cash loan of Rp.6,000,000,000.00 in which the cash is Rp.2,000,000,000.00 per month.Keywords : cost estimating, quantity surveyor, volume, upper structure, ApartementAbstrak: Estimasi biaya pekerjaan struktur atas pada setiap proyek konstruksi biasanya dilakukan oleh civil engineer atau arsitek. Namun, seiring berkembangnya ilmu pengetahuan, profesi baru seperti Quantity Surveyor telah menggeser tugas civil engineering atau arsitek dalam melakukan estimasi biaya. Studi kasus penelitian ini adalah pekerjaan struktur atas pada Apartemen The Accent yang dibangun pada lahan seluas 3.300 m2 dengan luas bangunan 27.000 m2. Metodologi penelitian dilakukan dengan cara studi literatur dan melakukan perhitungan volume menggunakan standar measurement method (SMM), sedangkan untuk harga satuannya sebagian diambil dari acuan Permen PU 45/PRT/M/2007. Dari hasil analisa perhitungan didapat total biaya keseluruhan pekerjaan struktur atas sebesar Rp. 51,162,851,482.23 dengan harga per m2 nya adalah 2,084,412.47/m2. Durasi pelaksanaan adalah selama 16 bulan. Untuk cash flow, cash in terdiri atas uang muka sebesar 10%, retensi sebesar 5%, progress pekerjaan bulanan dikurangi uang muka dan retensi, dan peminjaman kas kantor sebanyak Rp.6,000,000,000.00 yang mana cairnya dana adalah sebesar Rp.2,000,000,000.00 per bulannya.Kata kunci : Estimasi biaya, Quantity Surveyor, Volume, Struktur atas, Apartemen